2013
DOI: 10.1039/c3cc46005c
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the protein conformation to synthesize different-sized gold nanoclusters

Abstract: Gold nanoclusters with five discrete sizes (Au4, Au8, Au10, Au13, and Au25) are synthesized in a protein template with predefined conformation via a CO-mediated synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 38 publications
0
49
1
Order By: Relevance
“…Recently, Xie et al. reported a CO‐mediated method to synthesize AuNCs with different sizes (i.e., Au 4 , Au 8 , Au 10 , Au 13 , and Au 25 ) in BSA 18. They showed that the size of AuNCs was mainly dependent on the conformation of BSA.…”
Section: Protein‐directed Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Xie et al. reported a CO‐mediated method to synthesize AuNCs with different sizes (i.e., Au 4 , Au 8 , Au 10 , Au 13 , and Au 25 ) in BSA 18. They showed that the size of AuNCs was mainly dependent on the conformation of BSA.…”
Section: Protein‐directed Approachesmentioning
confidence: 99%
“…At pH 11, Au 25 was obtained due to the partially denatured conformation of BSA. However, no fluorescent properties of the synthesized AuNCs were reported 18…”
Section: Protein‐directed Approachesmentioning
confidence: 99%
“…They show unique moleculelike properties, such as quantized charging and luminescence. Several synthetic routes have been applied for the synthesis of fluorescent gold quantum clusters including a) templateassisted synthesis inside the matrix of folded protein, 30 dendrimer 31 and cyclodextrin 32 b) core-etching of metallic nanoparticles or some other large core size noble metal quantum clusters to few atoms nanoclusters, 33 c) chemical reduction of Au III ions using different reducing agents in presence of definite stabilizing/capping agents [34][35][36] and conversion of an as-synthesized quantum cluster into a larger size quantum cluster by ligand exchange with thiol-terminated ligands. [10][11][12][13][14][15][16][17][18][19][20][21][22] Small size of these noble metal quantum clusters with very low toxicity and lack of blinking property than semiconducting nanocrystals make them attractive candidates for biological imaging, [23][24][25][26] chemical sensing [27][28] and other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…18 The far-UV CD spectra of apo-a-LA in the absence of Hg 2+ shows two negative bands centered at 222 and 208 nm, which are characteristic of an a-helix. While the addition of [Hg 2+ ] up to 10 equivalents brings only marginal changes, the addition of up to 100 equivalents brings a signicant loss in the negative ellipticity of the band at 222 nm ( Fig.…”
Section: Resultsmentioning
confidence: 99%